The Effectiveness of the Education Package of Meta-diagnostic Treatment Based on the McMaster Model with Focus on Compassion, Awareness on Emotional Divorce and Marital Boredom among Women with Marital Conflict: A Pilot Study - Mandana Poorhejazi; Javad Khalatbari; Shohre Ghorban-Shiroudi; Anahita Khodabakhshi-Koolaee (Shahid Beheshti University of Medical Sciences, 2021)
Background and Objective: Marital conflicts are expected in a couple's life, and what matters is how they resolve conflicts. This education Package of transdiagnostic treatment has been created by considering several psychological factors in reducing marital conflicts and improving marital and communication relationships among couples. The objective of this study was to evaluate the effectiveness of the education package of meta-diagnostic treatment based on the McMaster model, focused on compassion, awareness on emotional divorce and marital boredom among women with marital conflict in West Tehran in 2019. Materials and Methods: This was a quasi-experimental applied study with pre-test, post-test, a control group, and quarterly follow-up. The statistical population of this study included all women with marital conflict who were referred to four selected counseling centers in the west of Tehran in the spring of 2019 who answered the questionnaire of marital conflict of Zana and Barati. 100 women who obtained the highest scores of marital conflict were selected, among whom 24 women were selected via convenience sampling method and randomly assigned to an experiment and a control group, each including 24 participants. Participants filled out the Guttman Emotional Divorce Scale and the Pineas Marital Boredom Scale in the pre-test. The experimental group underwent a 12-session training package, and then the control and experimental groups were retested after the intervention. Data were analyzed by multivariate analysis of covariance via SPSS software version 24. Results: The mean (SD) age of the experimental group was 35.3 (7.6), the control group 33.1 (4.3) years. The mean (SD) of the emotional divorce score of the experimental group decreased from 16.6 (1.3) in the pre-test to 14.2 (1.0) in the post-test and 14.5 (1.0) in the follow-up (P<0.001). The mean (SD) of the emotional divorce score of the control group was not significant. The mean (SD) of the marital boredom score of the experimental group decreased from 85.6 (8.8) in the pre-test to 67.5 (3.6) in the post-test and 67.9 (4.0) in the follow-up (P<0.01). The Changes in the marital boredom score of the control group was not significant Conclusion: The education package of meta-diagnostic treatment is effective in reducing emotional divorce and marital boredom in women with marital conflict.